Hubungan kadar hemoglobin dengan kualitas hidup pasien gagal ginjal kronik di Prodia Indramayu - Cahyani, Anak Agung Ayu Eka; Parwati, Putu Ayu; Asdiwinata, I Nyoman; Subhaktiyasa, Putu Gede; Rahayu, Lia (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Patients with chronic kidney disease have lower levels of hemoglobin, which causes them to become weak, easily tired, unproductive, and have a lower quality of life in their daily activities. According to the National Kidney Foundation (NKF) several things that can affect the quality of life of patients with chronic kidney disease are anemia with measuring hemoglobin levels so that managements is needed to achieve a good quality of life. The hemoglobin level of patients with chronic renal disease is low, this condition allows for clinical disturbances that affect quality of life. The purpose of this study was to determine the correlation between quality of life of chronic kidney disease patient dan hemoglobin at Prodia Indramayu. The research method used was observational analytic with a cross-sectional approach. The sample size in this study were 30 patients at Prodia Indramayu who has experienced chronic kidney disease and underwent hemodialysis for at least 6 months. The research was conducted from January – March 2023. Quality of life was measured using the WHOQOL-BREF questionnaire and hemoglobin results were obtained from secondary data from patient laboratory results. The results of the study obtained statistical data analysis using the Spearman test showing p value > 0.05, Sig.(2-tailed) 0.214>0.005, it can be concluded that there is no significant correlation between hemoglobin levels and quality of life in patients with chronic kidney disease.